Grandfather's Christmas tree - Strand, Keith (Silver Whistle/Harcourt Brace, 1999)
A grandfather tells how the family's Christmas tradition of placing a carved wooden nest with a pair of geese and their babies in the large spruce tree started years ago when his parents first settled in Colorado.